2001
DOI: 10.1038/sj.onc.1204460
|View full text |Cite
|
Sign up to set email alerts
|

Human fibroblast replicative senescence can occur in the absence of extensive cell division and short telomeres

Abstract: Ectopic expression of telomerase blocks both telomeric attrition and senescence, suggesting that telomeric attrition is a mitotic counting mechanism that culminates in replicative senescence. By holding human ®broblast cultures con¯uent for up to 12 weeks at a time, we con®rmed previous observations and showed that telomeric attrition requires cell division and also, that senescence occurs at a constant average telomere length, not at a constant time point. However, on resuming cell division, these long-term c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
62
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 47 publications
8
62
0
Order By: Relevance
“…The high molecular weight smears in the D17 experiment (particularly lanes 3 and 7) are often seen in keratinocyte TRF blots (Gordon et al, 2002) and are probably due to small amounts of 3T3 DNA contamination that gave a disproportionately high signal because mouse TRFs are 10-25 more abundant than in our human oral cultures. TRF measurements were carried out as described by Munro et al (2001), except that the blot was hybridized with a radiolabelled oligonucleotide probe (TTAGGG) 3 at 421C and subsequently washed in 6 Â SSC/1% SDS at 421C Figure 2 Telomerase activity in D30 and D17 cultures before and after infection with the hTERT expression vector. D30 cells were infected with hTERT or empty vector retroviruses at 9 PDs and analysed as soon as sufficient cells were available; D17 cells were infected at 39 PDs and analysed at 58 PDs.…”
mentioning
confidence: 99%
“…The high molecular weight smears in the D17 experiment (particularly lanes 3 and 7) are often seen in keratinocyte TRF blots (Gordon et al, 2002) and are probably due to small amounts of 3T3 DNA contamination that gave a disproportionately high signal because mouse TRFs are 10-25 more abundant than in our human oral cultures. TRF measurements were carried out as described by Munro et al (2001), except that the blot was hybridized with a radiolabelled oligonucleotide probe (TTAGGG) 3 at 421C and subsequently washed in 6 Â SSC/1% SDS at 421C Figure 2 Telomerase activity in D30 and D17 cultures before and after infection with the hTERT expression vector. D30 cells were infected with hTERT or empty vector retroviruses at 9 PDs and analysed as soon as sufficient cells were available; D17 cells were infected at 39 PDs and analysed at 58 PDs.…”
mentioning
confidence: 99%
“…The authors referred to this mode of cellular ageing as chronological lifespan (CLS). We and others have shown that quiescent human fibroblasts cultured for a long duration were unable to proliferate following replating at a lower cell density (Allsopp et al 1995;Munro et al 2001;Sarsour et al 2005;Sitte et al 1998). We observed that quiescent fibroblasts lost their proliferative capacity (measured as percentage of S phase at 48 h following replating of cells at a lower cell density) beginning from 30 days of quiescence; a maximal drop in S phase percentage was observed in cells replated from 60 days of quiescence (Sarsour et al 2005).…”
Section: Introductionmentioning
confidence: 68%
“…Although HT is an antioxidant, it can initially act as a prooxidant leading to the generation of superoxide and activation of MnSOD expression. Previous literature showed that long duration of quiescence resulted in a significant loss in the proliferative capacity of NHFs (Munro et al 2001;Sarsour et al 2005;Sitte et al 1998). We used contact-inhibited quiescent, but metabolically active cultures to study the effects of HT on CLS of NHFs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations